Established timeline? Motherhood depictions by professional women in Lima - Pariona Icochea, Tania (2019)
This text seeks to reflect on the conceptions of motherhood of a group of professional women living in Lima. We ask ourselves, how are they situated before the decision to be mother and how does motherhood fit into their life projects. The research is based on twenty-six interviews to professional women from different areas, in the age range of 28 to 38 years, who were not mothers at the time of the interview. Their answers show us a complex picture where various conceptions of motherhood coincide understanding it as a sacrifice of personal and professional life. The eagerness to balance work and family life with a motherhood project in an «established timeline» by social pressure makes the responses of these women at times contradictory, they also show the latent anguish of having to decide between motherhood or new ways of living.